Ectopic Salivary Gland Found in the Vocal Cord: A Rare Case - Shori Tajima; Niro Tayama; Fumihiko Matsumoto (Case Reports in Otolaryngology)
Introduction. Ectopic salivary gland is rarely found in the vocal cords; only two cases have been reported in the English literature. To the best of our knowledge, this is the third reported case of this anomaly. Case Presentation. A 78-year-old man with hoarseness two years ago visited our department. There were no other symptoms such as cough or sore throat. He had no history of smoking. Laryngeal endoscopic examination revealed a smooth mass in the anterior right vocal cord. We performed surgery under general anesthesia to remove the polyps and improve hoarseness. The histopathological specimen was reported to be salivary gland tissue. We diagnosed ectopic salivary glands of the vocal cord. Conclusion. It is necessary to consider the possibility of ectopic salivary glands as mass lesions of the vocal cords. Surgical resection is required and long-term follow-up is necessary after surgery.